Dinosaurs. The complete first and second seasons [videorecording (DVD)] - Pankin, Stuart; Walter, Jessica, 1941-2021; Willinger, Jason; Struthers, Sally (ABC Studios : Walt Disney Home Entertainment, 2016)
Comedy television series using state-of-the-art puppetry and audioanimatronics to create the Sinclairs a family of very modern dinosaurs whose antics and family relationships provide a humorous look at our own society.